Analysis of The Causal Relationship Between Money Supply, Foreign Reserves and Bank Credit in Oil Countries: Evidence From Iraq - Jayed, Ameen Fahad; Aldami, Abass K. (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This study investigates the causal relationships among money supply, foreign reserves, and bank credit in Iraq, a major oil-producing economy. Understanding these interconnected variables is crucial for effective monetary policy formulation and macroeconomic stability. this study employs the Toda-Yamamoto approach to Granger causality testing and quarterly data spanning from 2004 to 2022 to capture the dynamics following the Iraq War and explore the post-conflict economic landscape. Granger causality tests are conducted to determine the direction of causality among the variables. Impulse response functions and variance decompositions provide insights into the magnitude and persistence of shocks, shedding light on the relative importance of each variable in influencing the others. The empirical findings reveal a bidirectional causal relationship between money supply and foreign reserves, indicating that changes in one variable significantly influence the other. Additionally, a unidirectional causality is observed, running from foreign reserves to bank credit, highlighting the significance of foreign exchange reserves in facilitating bank lending. However, no causal link is detected between money supply and bank credit, suggesting that monetary policy may have limited direct impact on credit expansion in Iraq's banking sector. These results have important policy implications for the Central Bank of Iraq in managing monetary policy tools and navigating the challenges of an oil-dependent economy. The study contributes to the literature on monetary economics in resource-rich countries and provides valuable insights for policymakers and researchers alike.